The landscape of things. Issue 1 (2nd January 2018) - Kullmann, Karl
Abstract: As found in the Nordic tradition of the Ting and the proto-parliamentary German Ding, Things once pertained to landscape-based community assemblies for discussing matters of importance. Over time, as these forums moved indoors, the meaning of the word thing drifted towards its current use to refer to inanimate objects or events to which we are indifferent. Divested of its thingness, the concept of landscape also shifted from an active agent in cultural practice to a physical scene. Set within this historical context, the article explores design mechanisms for re-envisioning the landscape-thing in the present day. Drawing on concepts from the diverse cross-disciplinary field of thing theory, the article sketches a framework that considers the role, shape, and representation of contemporary landscape-things. This framework contributes to the advancement of landscape agency in the field.